EFEKTIFITAS SUPERVISI OLEH KEPALA SEKOLAH DALAM RANGKA PENINGKATAN KINERJA GURU SEKOLAH MENENGAH PERTAMA NEGERI 2 SELOMERTO KABUPATEN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The purpose of this research are (1) to determine how the performance of teachers in Junior High School 2 Selomerto Wonosobo ?, (2) to determine how the effectiveness of supervision conducted by the principal in order to improve the performance of teachers in Junior High School 2 Selomerto Wonosobo ? , (3) to determine whether the principal obstacles encountered in carrying out supervision visits classes in order to improve the performance of teachers in Junior High school 2 Selomerto Wonosobo ? .The research source in this research were citizens of Junior High School 2 Selomerto Wonosobo district , which consists of the principal, superintendent of education in the field of Junior High School Sub -District 6 Wonosobo district , committee , teachers, administrations , students in Junior High School 2 Selomerto Wonosobo .This research approach uses qualitative research approach , data collection procedures used were : (1) observation ,(2) interview and (3) dokumentation.And the technique of analyzing data that is descriptive analysis - qualitative , without the use of quantitative techniques and also the techniques of checking the validity of the data is done by a number of criteria including the degree of confidence ( credibility ) , the dependence ( dependability) , and certainty (confirmability) so that the data collected can be accountable.The results obtained are: (1) Teachers performance in Junior High School 2 Selomerto Wonosobo is good, because the teachers in Junior High School 2 Selomerto Wonosobo has done the duties based on the indicators of Teachers performance (2) supervision that is done by the Principal in the Context of Performance Enhancing Teacher Junior High School 2 Selomerto Wonosobo is very effective, it means that it must be done continuously and impronegly (3) the principal obstacles encountered in implementing classroom visit supervision to improve the performance of the teachers in Junior High School 2 Selomerto Wonosobo is the time constraint because the busy time.